Cantwell, Theresa Squires. Sepia photograph of two women from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
Left to right: Lucy Thorpe, and Margaret Jane Thorpe. Photograph by S. H. Parsons photography in St. John's, N.F. Lucy married a McDonough in Mass, USA, and Margaret was Theresa Squires' grandmother.